Session Initiation Protocol (SIP) - Suryawanshi, Amit; Bhati, Monika; Dubey, Rupesh (International Journal of Computer Sciences and Engineering, 2013)
Session Initiation Protocol (SIP) is a signaling protocol developed by SIP working group specified by the Internet Engineering Task Force (IETF), SIP is a text-based protocol similar to SMTP and HTTP, used to create, manage and terminate sessions on IP data network at application layer. A session could be a simple two-way telephone call or it could be a collaborative multi-media conference session. Such sessions include peer-to-peer voice, video, chat, interactive games, and virtual reality. This makes possible to implement services like voice-enriched e-commerce, web page click-to-dial or Instant Messaging with buddy lists on IP based data network resulting in reduced costs, improved customer service and easily manageable communications architecture. SIP is designed to address the functions of signaling and session management within a packet based telephony network. Signaling allows call information to be carried across the network boundaries. Session management provides the ability to control the attributes of an end-to-end call. In recent years, SIP has been the choice for services related to Voice over IP (VoIP). It is a standard (RFC 3261) proposed by Internet Engineering Task Force (IETF). SIP is still growing and being modified to take into an account all relevant features as the technology expands and evolves.